Observation of spin-dependent quantum jumps via quantum dot resonance fluorescence - Vamivakas, Nickolas A.; Lu, C.-Y.; Matthiesen, C.; Zhao, Ya; Fält, S.; Badolato, A.; Atatüre, M. (Nature, 2010)
A promising approach to realizing a practical qubit scheme for quantum computation involves the optical control of single electron spins in semiconductor quantum dots. Rapid progress towards the reliable preparation and manipulation of the quantum states of such spins has been achieved in recent years. The final challenge is to carry out 'single shot' measurements of the electron spin without interfering with it. Vamivakas et al. have now developed a technique that enables such a measurement through coupling of one quantum dot to another. This quantum dot 'molecule', unlike its single quantum dot counterpart, allows separate and independent optical transitions for state preparation, manipulation and measurement, avoiding the dilemma of relying on the same transition to address the spin state of an electron. As a result, the authors show, it is possible to observe spin quantum jumps in real time.